Chemical and heat resistance of silicone-acrylic-based binder and paint system on mild steel panels - Chew, K.W.; Arof, A.K.; Puteh, R. (EMERALD GROUP PUBLISHING LIMITED, 2007)
Purpose - This paper sets out to study the characteristics of silicone-acrylic-based resin and paint systems on mild steel panel for chemical resistance and high-temperature applications. Design/methodology/approach - Silicone resin has been incorporated into acrylic resin at various compositions. The mixed resins binders and paint systems have been characterised using physical test, acceleration test, electrochemical test and microstructure observation. Findings - The addition of silicone resin into acrylic resin showed significant improvement against high temperature. The results showed that coating film containing at least 30 per cent of silicone resin by weight was able to withstand high temperature of at least 250 degrees C. With the addition of titanium dioxide (TiO2) pigment into the best performing silicone-acrylic-based resin system, the system with pigment volume concentration of 30 per cent TiO2 showed the best performance which indicated the value of critical pigment volume concentration. The finding showed blistering formed in low-PVC systems and rusting in high-PVC systems. Research limitations/implications - Owing to the environmental issue, water-based silicone-acrylic resins should be explored to reduce the emission of harmful organic solvent. This can be done using solventless or powder coating technique. Practical implications - Silicone-acrylic resin coatings are a cost-effective high-temperature coating that have moderate resistance against corrosive environment such as marine water and also outdoor exposure with rain/sunshine cycles. Originality/value - The studies of this resin may give useful reference to other researchers.